2022
DOI: 10.1371/journal.pone.0272668
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutritional and hydration strategies during ultramarathon events between finishers and non-finishers: A systematic review protocol

Abstract: Ultramarathon running is a sport that is growing in popularity. Competing in an ultramarathon event is physiologically taxing on the human body, and it should not be surprising that not all individuals who enroll for an event ultimately finish. While many factors can contribute to this phenomenon, it is likely that nutritional and hydration strategies play a large role between finishing and not finishing an ultramarathon. No published paper has systematically reviewed the effects of nutritional and hydration s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Regarding electrolyte consumption, it was observed that the main changes were calcium ionic consumption and sodium ionic consumption, and higher levels of chlorine were noticed at the end of the effort. These led us to the fact that better hydration during long mountain races is required [59], as well as using a better vitaminization protocol before competing [60]. Subjects should revise their nutrition under strict recommendations from a nutrition specialist in order to reduce the damage produced by effort and to keep the main biochemical modifications within the physiological range.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding electrolyte consumption, it was observed that the main changes were calcium ionic consumption and sodium ionic consumption, and higher levels of chlorine were noticed at the end of the effort. These led us to the fact that better hydration during long mountain races is required [59], as well as using a better vitaminization protocol before competing [60]. Subjects should revise their nutrition under strict recommendations from a nutrition specialist in order to reduce the damage produced by effort and to keep the main biochemical modifications within the physiological range.…”
Section: Discussionmentioning
confidence: 99%